Case Report: Intrapulmonary Arteriovenous Anastomoses in COVID-19-Related Pulmonary Vascular Changes: A New Player in the Arena? - Qanadli, Salah D.; Rocha, Ana Carolina; Rotzinger, David C. (Frontiers in Medicine, 2021)
Up to now, COVID-19-related vascular changes were mainly described as thrombo-embolic events. A handful of researchers reported another type of vascular abnormality referred to as “vascular thickening” or “vascular enlargement,” without specifying whether the dilated vessels are arteries or veins nor providing a physiopathological hypothesis. Our observations indicate that the vascular dilatation occurs in the venous compartment, and underlying mechanisms might include increased blood flow due to inflammation and the activation of arteriovenous anastomoses.